IL-10 Dampens an IL-17–Mediated Periodontitis-Associated Inflammatory Network - Sun, Lu (J Immunol, 2020)
Emerging evidence suggests comprehensive immune profiling represents a highly promising, yet insufficiently tapped approach to identify potentially prognostic signatures for periodontitis. In this report, we agnostically identified a periodontitis-associated inflammatory expression network with multiple biomarkers identified within gingival crevicular fluid samples from study participants by applying principal component analysis. We identified an IL-17–dominated trait that is associated with periodontal disease and is inversely modified by the level of IL-10. IL-10 mitigated chemokine CXCL5 and CXCL1 expressions in IL-17–stimulated peripheral blood monocytic cells and peripheral blood monocytic cell–derived macrophages. Il10-deficient mice presented more bone loss, which was associated with more Il17 and IL-17–mediated chemokine and cytokine expression at the transcriptional levels in comparison with control wild-type mice in both the Porphyromonas gingivalis–induced experimental murine periodontitis and ligature-induced alveolar bone-loss models. The dampening effect of IL-10 on the excessive signaling of IL-17 appeared to be mediated by innate immune cells populations rather than by gingival epithelial cells, which are the major cell target for IL-17 signaling. Additionally, elevated IL-17 response in Il10-deficient mice specifically elicited an M1-skewing macrophage phenotype in the gingiva that was associated with the advanced bone loss in the ligature model. In summary, IL-17 dominated an inflammatory network characteristic of periodontitis, and IL-10 dampens this excessive IL-17–mediated periodontitis trait.